2012
DOI: 10.1159/000334659
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Axillary Lymph Node Fine Needle Aspiration in Breast Cancer Staging prior to Chemotherapy with Histological Correlation

Abstract: Objective: Axillary lymph node (LN) sampling is important for breast cancer staging and can be performed using fine needle aspiration (FNA). The aim of this study is to review the axillary LN FNAs performed at our institution prior to treatment, and to correlate their results with the available LN histology in order to evaluate the diagnostic utility of FNA. Study Design: A total of 130 cases were retrospectively identified over a 1-year period and reviewed. The FNA findings were correlated with the histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…Numerous studies have established the fact that preoperative use of image-guided axillary lymph node FNA obviates the need for sentinel lymph node biopsy in positive cases and helps to select prompt systemic therapy [2,3,4]. Several studies have reported the sensitivity and specificity of axillary FNA to be in the range of 50-85 and 98-100%, respectively [5,6]. Similarly, our study showed 91.7 and 100% sensitivity and ‘true' specificity (after excluding 5 ‘false positive' cases with subsequent postneoadjuvant negative histology), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have established the fact that preoperative use of image-guided axillary lymph node FNA obviates the need for sentinel lymph node biopsy in positive cases and helps to select prompt systemic therapy [2,3,4]. Several studies have reported the sensitivity and specificity of axillary FNA to be in the range of 50-85 and 98-100%, respectively [5,6]. Similarly, our study showed 91.7 and 100% sensitivity and ‘true' specificity (after excluding 5 ‘false positive' cases with subsequent postneoadjuvant negative histology), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative evaluation of the axillary lymph nodes has become standard in the management of patients with carcinoma of the breast . It is playing an increasing role in the planning of further management, including surgical approach and neoadjuvant systemic therapy . Definitive nodal staging is based on surgical pathologic evaluation of sentinel lymph node(s) or axillary dissection specimens .…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant treatment is being used increasingly, not only for cases considered inoperable, but for any case in which preoperative evaluation demonstrates a potential benefit for cytotoxic chemotherapy . This depends not only on size, estrogen receptor (ER), progesterone receptor (PgR), and human epidermal growth factor receptor 2 oncoprotein (HER2) status, but also on the result of diagnostic axillary FNA . In a significant subset of neoadjuvant cases, subsequent surgical staging is challenging because of complete or near‐complete treatment response of the tumor .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations